Intersektionelle Filmanalyse in der fremdsprachigen Kulturdidaktik am Beispiel des MigrantInnenbildes in ausgewählten Culture-Clash-Komödien - Lis, Tomasz; Janachowska-Budych, Marta (Glottodidactica, 2019)
The aim of the following paper is to discuss the image of migrants presented in selected culture-clash comedies, and its didactical contribution to transcultural learning. The intersectional analysis of three film sequences conducted in the framework of university classes (seminars and workshops) on intercultural communication is described as a starting point for discussion and reflection upon the stereotyped, and popularised images of migrants as people with specific qualities and skills, certain social backgrounds, and typical patterns of behaviour. The critical analysis of such images supports transcultural learning, which is understood, among others, as bringing aspects of the development of individual as well as collective identities into question, and acknowledging heterogeneity and diversity as cultural and social enrichment.